Real‐life glecaprevir/pibrentasvir in a large cohort of patients with hepatitis C virus infection: The MISTRAL study. (2nd July 2019) - Persico, Marcello; Aglitti, Andrea; Milella, Michele; Coppola, Carmine; Messina, Vincenzo; Claar, Ernesto; Gentile, Ivan; Sogari, Fernando; Pierri, Paola; Surace, Lorenzo A.; Morisco, Filomena; Tundo, Paolo; et al.
Abstract: Background and aims: It is paramount to identify predictors of treatment failure with direct antiviral agents in 'field‐practice' patients, including people who inject drugs (PWID). Data on the efficacy of glecaprevir/pibrentasvir (GLE/PIB) in a field‐practice scenario are scant. The multicentre MISTRAL study enrolled 1177 patients, including PWID, to assess real‐life efficacy and safety of GLE/PIB and to identify the predictive factors for this treatment. Methods: This was a prospective, longitudinal study. The outcome variable was the rate of sustained virological response (SVR) at week 12. Results: A total of 123 patients (10%) were infected from hepatitis C virus (HCV) 3. METAVIR fibrosis score was F4 in 104 subjects (9%); 118 patients (10%) were PWID. Overall, 1163/1177 (99%) patients achieved SVR. The baseline clinical factors discriminating between treatment success and treatment failure were age at treatment ( P  = 0.031) and creatinine level ( P  = 0.034). SVR rates were not influenced by gender, substance abuse, previous treatment, treatment duration, fibrosis or chronic kidney disease stage. Compared with non‐substance users, the 118 PWID exhibited a significantly different genotype pattern distribution ( χ 2  < 0.001). A total of 40/118 (33.9%) of substance users were HCV3 compared to 83/1056 (7.9%) non‐substance users. Only 6 patients (0.5%) reported a serious adverse event. Conclusions: The MISTRAL study provides evidence of GLE/PIB efficacy in a field‐practice scenario in a highly epidemic HCV area in southern Italy; it unveiled significant differences in genotype distribution among the most underserved and difficult‐to‐treat patient subgroups including PWID.